Sense and Feel - Muniba Saeed; Amnah Moghees; Saima Abbas Dar (Linguistics and Literature Review, 2018)
Translation of poetry is a hard nut to crack. Especially, when it is loaded with cultural connotations. Beyond any doubt, translation demands linguistic and cultural skills from a translator to express meanings. Hence, the process of translation becomes challenging when both the source language and the target language belong to two different language families. The present study explores the linguistic challenges faced by translators when translating Faiz Ahmad Faiz’s Urdu poetry into English. The researchers have found that translating Urdu metaphorical expressions and compound words used in Faiz’s Urdu poetry is near to impossible as these expressions are rooted in specific cultural, social, political and historical backgrounds.